ANALISIS BEHAVIORAL INTENTIONS PENGGUNAAN APLIKASI SAMBARA DENGAN METODE UTAUT DI KOTA BANDUNG - Deril Festinoval (Jurnal Administrasi Publik, 2023)
Â  The Government of Bandung has successfully developed innovative solutions to enhance the quality of public services, aimed at addressing the challenges within the city and providing the most effective and efficient services to the community. One of the initiatives undertaken is the launch of the Sambara application. This study aims to identify public acceptance and the affecting factors pertaining to the utilization of the Sambara application, one of the e-government programs in Bandung, using the Unified Theory of Acceptance and Use of Technology (UTAUT) method. The research employs a quantitative approach, utilizing a survey method. The cluster sampling technique is employed, involving a total of 100 participants who responded to the questionnaire. Data analysis is conducted using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). Based on the test results, it can be concluded that both performance expectancy and facilitating conditions have a positive and significant impact on behavioral intentions. Effort expectancy, on the other hand, has a positive but insignificant effect on behavioral intentions. Meanwhile, social influence demonstrates a negative impact on the behavioral intentions for utilizing the Samsat Mobile Jawa Barat (Sambara) application in Bandung.